The Green Campus Concept Implementation Based on Environmental and Infrastructure Arrangements: A Case Study of Sports Center Facilities and Infrastructure University of Papua, Indonesia - Marsudi, H.R. Partino, Bambang Nugroho, Roni Bawole, Syafrudin Raharjo, Anton Sineri, D. S. Mabuid, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Sustainable development is a modern-day development goal. To realize these conditions, all countries, including Indonesia, are required to implement sustainable development goals. It is also the goal of building higher education infrastructure, particularly in Indonesia. This research aims to evaluate and quantify the green campus score on the development of sports infrastructure at the University of Papua, Manokwari. Questionnaires are used to collect data in the quantitative method. The UI green metric method is used to assess the green campus level. In addition, a SWOT analysis is performed to evaluate the work's implementation. The results indicated that it had been adequately implemented, according to the findings of an analysis of green campus indicators at the UNIPA Campus's sports center infrastructure. Only a few indicators remain to be improved in the construction of a sports center on the UNIPA Campus, such as management and monitoring of development implementation, use of environmentally friendly tools, management and monitoring of impacts caused by development activities, and campus providing regular budgets for care and maintenance of facilities and infrastructure. On the other hand, the other indicators have been rated as good field implementation. Based on the SWOT analysis results, the strategy for structuring the environment and green campus infrastructure at the UNIPA campus sports center infrastructure must pay attention to the threats that may arise as a result of the sports center construction, such as environmental degradation, the emergence of new residential clusters not following the UNIPA campus, and the emergence of new residential clusters not under the UNIPA campus.